PERAN CITRA MEREK MEMEDIASI PENGARUH KEPUASAN PELANGGAN TERHADAP NIAT MENGGUNAKAN KEMBALI E-COMMERCE LAZADA - Anggraeni, Ni Gusti Ayu Putri; Wulandari Kusumadewi, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p19, 2023)
Lazada is one of the largest e-commerce applications in Indonesia. In order to survive in the business, Lazada must ensure that its users are willing to reuse the application on an ongoing basis. The purpose of this study is to explain the effect of customer satisfaction on intention to reuse Lazada e-commerce users in Badung which is mediated by brand image. The sample used is 100 respondents who have done online shopping at Lazada and are domiciled in Badung. Samples were obtained using purposive sampling. Data was collected by distributing online questionnaires. Data was analyzed using path analysis and Sobel test. The results found that customer satisfaction has apositive significant effect on intention to reuse, customer satisfaction has  positive significant effect on brand image, brand image has  positive significant effect on intention to reuse and brand image mediates the effect of customer satisfaction on the intention to reuse e-commerce Lazada.